Thermal propoerty measurement of nanofluid - Kwek, Ding Tian. (2010)
Nanofluids are new kinds of fluids engineered by dispersing nanoparticles in base fluids. This report presents an experimental investigation of thermophysical properties of Al2O3 nanofluids. Al2O3 nanofluids were prepared by adding surfactant and undergoing ultrasonication. After which, the thermal conductivity, viscosity and surface tension were measured. Thermal conductivity is determined using the transient hot wire experiment. The results show that the thermal conductivity of Al2O3 nanofluids increases with increasing nanoparticle concentrations in a distinct linear fashion. It is found that adding a small volume percentage, 1 to 5% of Al2O3 nanoparticles in water significantly increases the effective thermal conductivity of Al2O3 nanofluids by 6 to 20% respectively. It was further observed that a dramatic increase in the enhancement of conductivity takes place with temperature. With 1% nanoparticles at 15°C, the enhancement is about 1.7%, but at 55°C this value increases to about 16%. This finding makes nanofluids even more attractive as cooling fluid for devices with high energy density where the cooling fluid is likely to work at a temperature higher than the room temperature. Results also indicate that particle size is an important parameter for effective thermal conductivity. As particle sizes increase from 10 nm to 35 nm, thermal conductivity enhancement decreases from 30% to 10%. Enhancement starts to increase when particle size is above 35 nm. The increase in thermal conductivity is ~27.5% for particle size of 150 nm. Viscosity measurements were conducted with the rotational rheometer. The shear thinning effect observed by some of the researchers is caused by agglomeration. We observe that after re-ultrasonification, at volume concentrations 1-5%, nanofluids exhibit Newtonian behaviour. The effective viscosity increases as volume concentrations increases. At 5% volume concentration, there is an increment of 60% in viscosity. As temperature increases, the viscosity of Al2O3 nanofluids decreases exponentially. However, the effective viscosity ratio against temperature shows that above 35°C, the decrease in viscosity is not as effective. The experimental results also indicate that when nanoparticle size is smaller, the viscosity of nanofluids is much larger. At 5% volume concentration and particle size of 10 nm, there is increment in viscosity by 80%. Lastly, surface tension measurement is conducted using the FTA 200 equipment. Results indicate that particle volume concentration has negligible effect on the surface tension. The decrease in surface tension is likely due to the addition of surfactant Cetyltrimethylammonium Bromide (CTAB), which changes the surface properties of nanofluids.